Pengaruh Program Pengendalian Resistensi Antimikroba terhadap Penggunaan Antibiotik Profilaksis pada Bedah Obstetri dan Ginekologi - Winarni Winarni; Nanang Munif Yasin; Tri Murti Andayani (Faculty of Pharmacy, Universitas Gadjah Mada)
The incidence of surgical site infections (SSI) in obstetric and gynecological surgery is quite high. Rational prophylactic antibiotics in surgery are important strategies for the prevention of SSI. Antimicrobial Stewardship Program (ASP) for rational prophylactic antibiotic use has been carried out. This study aims to determine the rationality of the use of prophylactic antibiotics and incidence rate of SSI, the effect of ASP on the rationality of prophylactic antibiotics and clinical outcomes in obstetric and gynecology surgery. This study used a quasi-experimental pretest postest design without control group with retrospective data collection. Research time for 2 months from May to June 2019. The subjects of this study were obstetric and gynecology surgery patients at Pandan Arang Hospital Boyolali in 2018 who were divided into 2 groups: patients before the ASP and patients after the ASP with a total sample of 93 patients each group. An evaluation of the type, dose, time of administration, route of administration, and duration of prophylactic antibiotics were performed against the standard. Data analysis used the Pearson Chi-square test to see the relationship between rationality and clinical outcomes with ASP. The rationality of prophylactic antibiotic use increased from 0 (0%) cases before the ASP to 52 cases (55.9%) after the ASP. The SSI incidence rate before ASP was 9.7%, down to 4.3% after ASP. There was a significant relationship between the rationality of prophylactic antibiotics and ASP (p <0.05) but the relationship between clinical outcome (SSI incidence) and ASP was not significant (p> 0.05). The result of this study can be used to promote the implementation of ASP in other wards to increase rational use of antibiotics.